Grafismo e discurso identitário indígena potiguara da Paraíba no século XXI - Falcão, Emmanuel de Sousa Fernandes (2022)
The present research approaches body painting as an identity language of the Potiguara peoples. The objective of the thesis is to build a linguistic theory of Potiguara body painting, based on Bakhtin, communicating the scientific community about the possible claims made by these non-verbal linguistic codes. The object of study are the practices of body painting that are relevant in some social markers of the Potiguara identity. The problem is correlated with the need to understand the the voices and discourses said by Potiguara body painting. Thus, the thesis has as its object of study the Potiguara body painting, in particular, its presence in the educational-religious practices that these people use as a communicative method. The general objective is to analyze the relationship between the Potiguara indigenous body painting from Paraíba and the identity representations of those who practice it. The specific objectives are limited to: Investigating the contemporary Potiguara indigenous identity; examine the theoretical relationship between scientific literature, identity, language and body painting and; register the Potiguara indigenous claims said by Potiguara body painting. This is a qualitative type of research; basic; descriptive; and with ethnographic methods, punctuating literary review in 349 different bibliographic references, from 290 authors, dated between 1839 and 2022. The unprecedented character of the study is subdivided into three points. They are: Body paintings are expressions that also claim identity recognition, therefore, it updates some studies prior to the thesis, regarding new linguistic codes created or implemented by new concepts; the body painting is a language: political, religious and artistic, with the intention of saying something to someone, so among the speeches that Potiguara body painting intones is the need to rethink the visibility that higher education institutions in Brazil promote to native peoples and, finally, it brings the scientific community a thesis with hyperlinks that complement the verbal record, adding images, voices, videos, music and other elements that dialogue with the text. Among the final considerations of the research, it was conclusive that the Potiguara body painting tends to expand, with the potential for the elaboration of new symbols or the attribution of new concepts to body painting that already transit in the community of this people. In this way, Potiguara body painting transcends mere aesthetics and, despite having shared meanings, historically and culturally, Potiguara body painting can have peculiar nuances of meaning for those who are painted with its symbols. The Potiguara understand it is relevant to occupy spaces to be able to sing their speeches and, among these spaces, they share their voices, through this thesis, so that higher education institutions can tell their stories and register their claims. The possibilities for future studies that this thesis can incite are in the perspective that the Potiguara claims are not just for identity recognition and, thus, despite highlighting one of the Potiguara requests, many others, even those supported by law, continue eclipsed. Thus, the Potiguara body painting expresses respect for its own worldviews, calls for environmental awareness and, among so many other discourses, announce points that were not the object of study of the research, endorsing the need to revisit these people, and other ethnicities, with the aim of continuing to bring the voices of Native Peoples to academic spaces.